Róger Rumrrill García: Amazonia and Interculturality - Vásquez Rodríguez, Rafael (2024)
Róger Rumrrill García, a writer and journalist from Loreto, spent his adolescence in various towns in the Peruvian jungle. To date, he has published 32 books that address the subject of the Amazon from history, essay, narrative, film script, poetry and journalism, from a multidimensional and holistic perspective. His work has received several awards, including the Premio Casa de la Literatura Peruana awarded by the Ministry of Education and recognition as a Meritorious Personality of Peruvian Culture by the Ministry of Culture, both granted in 2023. Among his most recent publications are the book of short stories Narraciones de la Amazonía, the novel biography Miguelina about the iconic and paradigmatic life of the yurimagüina Miguelina Acosta Cárdenas and the novel La Virgen del Samiria, which is part of a narrative saga about the Amazonian utopia. The second volume is entitled Las Estirpes Amazónicas, always exploring the myth of the Amazonian utopia installed in the literature of the Peruvian Amazon.